Potential Role of CXCR4 Targeting in the Context of Radiotherapy and Immunotherapy of Cancer - Eckert, Franziska; Schilbach, Karin; Klumpp, Lukas; Bardoscia, Lilia; Sezgin, Efe Cumhur; Schwab, Matthias; Zips, Daniel; Huber, Stephan M. (Frontiers in Immunology, 2018)
Cancer immunotherapy has been established as standard of care in different tumor entities. After the first reports on synergistic effects with radiotherapy and the induction of abscopal effects – tumor shrinkage outside the irradiated volume attributed to immunological effects of radiotherapy – several treatment combinations have been evaluated. Different immunotherapy strategies (e.g. immune checkpoint inhibition, vaccination, cytokine based therapies) have been combined with local tumor irradiation in preclinical models. Clinical trials are ongoing in different cancer entities with a broad range of immunotherapeutics and radiation schedules. SDF-1 (CXCL12)/CXCR4 signaling has been described to play a major role in tumor biology, especially in hypoxia adaptation, metastasis and migration. Local tumor irradiation is a known inducer of SDF-1 expression and release. CXCR4 also plays a major role in immunological processes. CXCR4 antagonists have been approved for the use of hematopoietic stem cell mobilization from the bone marrow. In addition, several groups reported an influence of the SDF-1/CXCR4 axis on intratumoral immune cell subsets and anti-tumor immune response. The aim of this review is to merge the knowledge on the role of SDF-1/CXCR4 in tumor biology, radiotherapy and immunotherapy of cancer and in combinatorial approaches.